2001
DOI: 10.1002/nbm.713
|View full text |Cite
|
Sign up to set email alerts
|

Proton T1 and T2 relaxation times of human brain metabolites at 3 Tesla

Abstract: Longitudinal and transverse relaxation times were measured for proton MRS signals from human brain metabolites at 3 T using a short-echo STEAM protocol and a surface coil as a transmitter/receiver. Volumes of interest containing mostly grey or mostly white matter were selected in occipital lobes of healthy subjects and relaxation times for the following resonances were obtained: N-acetylaspartate at 2.01 ppm (T(1) and T(2)), glutamate at 2.35 ppm (T(1)), creatine at 3.03 and 3.92 ppm (T(1) and T(2)), choline-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
272
7
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(314 citation statements)
references
References 21 publications
33
272
7
2
Order By: Relevance
“…The benefits are especially expected to be important for metabolites having low concentration or overlapping spectral lines and for compounds giving complex J-coupled spectral patterns. Recent studies, however, have indicated that these advantages may be partially offset by a decrease of T 2 and T Ã 2 with increasing static magnetic field [2,3], with some predicting [4] a moderate increase of the signalto-noise ratio (SNR) and a nearly linear increase in the spectral linewidth (expressed in Hz) when increasing B 0 above 9.4 T.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits are especially expected to be important for metabolites having low concentration or overlapping spectral lines and for compounds giving complex J-coupled spectral patterns. Recent studies, however, have indicated that these advantages may be partially offset by a decrease of T 2 and T Ã 2 with increasing static magnetic field [2,3], with some predicting [4] a moderate increase of the signalto-noise ratio (SNR) and a nearly linear increase in the spectral linewidth (expressed in Hz) when increasing B 0 above 9.4 T.…”
Section: Introductionmentioning
confidence: 99%
“…Determining their relaxation constants from experimental data collected with spin-echo sequences is common in diffusion tensor imaging (DTI) and spectroscopy (DTS) [1][2][3], measurements of fractional anisotropy (FA) [4], transverse relaxation rates (R 2 ) [5][6][7], etc. An exponentially decaying signal can be described by two parameters: its amplitude ρ and decay rate λ, (1) where t is the user-controlled encoding parameter (diffusion weighting or echo time).…”
Section: Introductionmentioning
confidence: 99%
“…While the T 1 relaxation time of water protons is significantly longer at 3 T as compared to 1.5 T, metabolite T 1 measurements can be either longer [34] or almost unchanged [35,36]. The discrepancies can be explained by the large interindividual variability at 1.5 T and the possible differences in scanner performance, sequence design and strategies for acquiring and evaluating spectra.…”
Section: Spectral Resolution and Metabolite Quantificationmentioning
confidence: 99%